TRANSFORMATION OF AUDIT SERVICE: Guzal Yashinovna Babaeva, Sagdiana Doniyor qizi Namozova (Ustozlar uchun, 2024)
In this paper, the authors attempt to formulate a new definition of the concept of modern audit as a process in which internal auditors use information and communication technologies (ICT) in conjunction with analytical procedures to collect electronic evidence, interact with the auditee, and prepare a report on the reliability of financial data and internal control systems regardless of the auditor's physical location. Based on research on virtual teams and analysis of internal audit activities, we present a research framework that defines the areas in which ICT and automated audit analytics allow auditors to work remotely, reduce travel expenses and wait times, and improve efficiency and coverage.